Impact of Active Learning Strategy on the Student Engagement - Munna, Afzal Sayed; Kalam, Md Abul (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Economic development has encouraged innovation in a range of industries; however, the education industry has been following traditional modes of teaching until recently across the world. This has not only affected the capabilities of the youth but has also led to the problem of unemployment and diminished success rates at the workplace. One of the factors contributing to this situation is the lack of student engagement. In this research, we examined the factors affecting student engagement among higher education students and determining the impact of pedagogical approaches with active leaning on influencing the engagement level. Analysis of 50 higher education level 3-7 students has shown that the major hinderance in student engagement is assessing their current knowledge levels to teach lessons effectively. Hence, using practical knowledge impartation mechanisms such as gamification, collaborative and peer learning would improve the cognitive, learning, and emotional behaviour of students; thus, boosting the engagement level.